Diacylglycerol at the inner nuclear membrane fuels nuclear envelope expansion in closed mitosis - Foo, Sherman; Cazenave-Gassiot, Amaury; Wenk, Markus R.; Oliferenko, Snezhana (Journal of cell science, 2023)
Nuclear envelope (NE) expansion must be controlled to maintain nuclear shape and function. The nuclear membrane expands massively during closed mitosis, enabling chromosome segregation within an intact NE. Phosphatidic acid (PA) and diacylglycerol (DG) can both serve as biosynthetic precursors for membrane lipid synthesis. How they are regulated in time and space and what the implications are of changes in their flux for mitotic fidelity are largely unknown. Using genetically encoded PA and DG probes, we show that DG is depleted from the inner nuclear membrane during mitosis in the fission yeast Schizosaccharomyces pombe, but PA does not accumulate, indicating that it is rerouted to membrane synthesis. We demonstrate that DG-to-PA conversion catalyzed by the diacylglycerol kinase Dgk1 (also known as Ptp4) and direct glycerophospholipid synthesis from DG by diacylglycerol cholinephosphotransferase/ethanolaminephosphotransferase Ept1 reinforce NE expansion. We conclude that DG consumption through both the de novo pathway and the Kennedy pathway fuels a spike in glycerophospholipid biosynthesis, controlling NE expansion and, ultimately, mitotic fidelity.